Detoxification and immobilization of chromite ore processing residue using the alkali-activated cementitious materials mixed with ascorbic acid. (1st July 2020) - Xia, Ming; Muhammad, Faheem; Zhao, Shujie; Yu, Lin; Lin, Huirong; Huang, Xiao; Jiao, Binquan; Shiau, Yan Chyuan; Li, Dongwei
Abstract: The existence of leachable Cr(Ⅵ) in chromite ore processing residue (COPR) makes it hazardous waste. Therefore, resourceful utilization of COPR is necessary to protect the ecosystem and living biota from hazardous effect of Cr(Ⅵ) caused by its leaching. In this study, detoxification and immobilization of COPR was carried out through introduction of ascorbic acid (AA) in alkali-activated cementitious materials. Several dosages of AA were treated with water extractable/soluble Cr(Ⅵ) to achieve the optimum dosage which could be further utilized in solidification process. While, the compressive strength was developed through utilizing different modulus of water glass, liquid to solid ratios and curing temperatures. The results showed that 0.3% of AA was enough to reduce the Cr(Ⅵ) into Cr(Ⅲ), and highest compressive strength of 120 MPa was achieved after using the modulus of 1.6, liquid to solid ratio of 0.24 and curing temperature of 30 °C. The solidified samples having AA had not exceeded the toxicity limit up to 60% addition of COPR, and samples without addition of AA were effective for solidification of 20% COPR. Regarding mechanism, the compressive strength, leaching behavior and microscopic analysis i.e. X-ray diffraction (XRD), Fourier transform infrared spectrometry (FTIR) and scanning electron microscope with energy dispersive spectrometry (SEM-EDS) showed that immobilization of chromium was carried out through physical and chemical means. Highlights: COPR was immobilized by alkali-activated cementitious materials with ascorbic acid. The solidified product has a great compressive strength for construction purpose. Significant results are achieved regarding solidification efficiency of COPR.